2015
DOI: 10.1007/978-3-662-48797-6_29
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Approach to MPC with Preprocessing Using OT

Abstract: Abstract. SPDZ, TinyOT and MiniMAC are a family of MPC protocols based on secret sharing with MACs, where a preprocessing stage produces multiplication triples in a finite field. This work describes new protocols for generating multiplication triples in fields of characteristic two using OT extensions. Before this work, TinyOT, which works on binary circuits, was the only protocol in this family using OT extensions. Previous SPDZ protocols for triples in large finite fields require somewhat homomorphic encrypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…The M4R method gets half the latency of the vector method in this scenario, since the number of rounds is halved. As discussed earlier, the preprocessing for LowMC would likely be much better than AES if implemented with the protocol of [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M4R method gets half the latency of the vector method in this scenario, since the number of rounds is halved. As discussed earlier, the preprocessing for LowMC would likely be much better than AES if implemented with the protocol of [29].…”
Section: Resultsmentioning
confidence: 99%
“…Note that LowMC only requires multiplication triples in F2, for which the protocol of [29] could be much faster than 4 The experiments in [31] showed that communication is the main bottleneck of the protocol, so this should give an accurate estimate. using F 2 128 triples.…”
Section: Lan Wanmentioning
confidence: 99%
“…If any of these checks fails, abort. Similarly to prior constructions such as [DPSZ12,NNOB12,FKOS15,KOS16], our protocol is in the pre-processing model where the main difference is that the computation is carried out via two random committees P (h) and P (1) . The preprocessing phase is function and input independent, and provides all the correlated randomness needed for the online phase where the function is securely evaluated .…”
Section: Check Consistency Of the Inputs As Followsmentioning
confidence: 99%
“…In [31], a single non-XOR gate is estimated to require ca. 70µs during preprocessing (with two parties).…”
Section: Complexity Of Actively Secure Integer Multiplication and Aesmentioning
confidence: 99%
“…In concurrent work [36], the oblivious transfer methods of [31] have been extended to construct SPDZ multiplication triples over Z p . They report amortized timings of ca.…”
Section: Complexity Of Actively Secure Integer Multiplication and Aesmentioning
confidence: 99%